1987
DOI: 10.3109/00048678709158911
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Treatment of Tricyclic-Resistant Depression: Review and Management Guidelines

Abstract: Despite the introduction of a wide range of antidepressant drugs since the late 1950s, approximately 30-50% of depressed subjects do not respond to these agents. Various treatment strategies, both pharmacological and non-pharmacological, have been proposed for treatment-resistant depression. This paper critically reviews the studies of single and combined pharmacological treatments for tricyclic-resistant patients, with a particular discussion of lithium augmentation. The major inadequacies of these studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In addition to specific pharmacological and ECT studies, such as assessing carbamazepine for treatment-resistant depression (Cullen et al 1991) and ECT practices in Australasia (O'Dea et al 1991), MDU staff have prepared a number of treatment guidelines, including papers on bipolar disorder and pharmacological treatment of tricyclic-resistant depression (Mitchell, 1987), while Tanner & Ball (1989) have prepared a self-help manual focusing on cognitive and behavioural strategies for overcoming depression, and Eyers et al (1993, submitted) have undertaken patient satisfaction studies that, in turn, have suggested modifications to ward and out-patients' procedures.…”
Section: Treatment Studiesmentioning
confidence: 99%
“…In addition to specific pharmacological and ECT studies, such as assessing carbamazepine for treatment-resistant depression (Cullen et al 1991) and ECT practices in Australasia (O'Dea et al 1991), MDU staff have prepared a number of treatment guidelines, including papers on bipolar disorder and pharmacological treatment of tricyclic-resistant depression (Mitchell, 1987), while Tanner & Ball (1989) have prepared a self-help manual focusing on cognitive and behavioural strategies for overcoming depression, and Eyers et al (1993, submitted) have undertaken patient satisfaction studies that, in turn, have suggested modifications to ward and out-patients' procedures.…”
Section: Treatment Studiesmentioning
confidence: 99%